Implementation of a flipped classroom approach to promote active learning in the third-year surgery clerkship - Lewis, Catherine E.; Chen, David C.; Relan, Anju (The American journal of surgery, 2018)
Constructivist student-centered instructional models such as the flipped classroom (FC) have been shown to improve learning. A FC approach was implemented for the surgery clerkship. Data was collected in phase 1 to evaluate student learning and attitudes. Based on these results, questions for the phase 2 open-ended survey were developed to improve understanding of learner attitudes, and ascertain how well the FC aligns with constructivist principles. There was no significant difference in shelf exam performance between the control and intervention groups. A majority of students agreed that they preferred the FC over lectures, and that their learning improved. Open-ended survey analysis demonstrated that the FC fostered self-directed, active learning, and that the in-class sessions facilitated application of concepts and deeper learning. Areas identified for improvement included better alignment with learning preferences through greater variety of pre-class learning options, improvement of podcast technical quality, and utilization of smaller in-class discussion groups. Students had a positive perception of the FC. The FC supports self-directed and more active and deeper in-class learning.